Electrochemically Nanostructured Polyvinylferrocene/Polypyrrole Hybrids with Synergy for Energy Storage. (24th June 2015) - Tian, Wenda; Mao, Xianwen; Brown, Paul; Rutledge, Gregory C.; Hatton, T. Alan
Abstract : Unconjugated redox polymers, such as polyvinylferrocene (PVF), have rarely been used for energy storage due to their low intrinsic conductivity. Conducting polymers with conjugated backbones, though conductive, may suffer from insufficient exposure to the electrolyte due to the often formed nonporous structures. The present work overcomes this limitation via simultaneous electropolymerization of pyrrole and electroprecipitation of PVF on electrode surfaces. This synthesis method relies on the π–π stacking interactions between the aromatic pyrrole monomers and the metallocene moieties of PVF. This fabrication process results in a highly porous polymer film, which enhances the ion accessibility to polypyrrole (PPy). PPy serves as a "molecular wire, " improving the electronic conductivity of the hybrid and the utilization efficiency of ferrocene. The PVF/PPy hybrid exhibited a specific capacitance of 514.1 F g −1, which significantly exceeds those of PPy (27.3 F g −1 ) and PVF (79.0 F g −1 ), respectively. This approach offers an alternative to nanocarbon materials for improving the electronic conductivity of polymer hybrids, and suggests a new strategy for fabricating nanostructured polymer hybrids. This strategy can potentially be applied to various polymers with π‐conjugated backbones and redox polymers with metallocene moieties for applications such as energy storage, sensing, and catalysis. Abstract : The π–π stacking interactions between aromatic monomers and metallocene moieties are exploited via simultaneous electroprecipitation of polyvinylferrocene and electropolymerization of pyrrole to form a highly porous redox‐responsive hybrid. The resulting synergistic enhancement of the utilization efficiency of ferrocene and the accessibility of ions to polypyrrole leads to the significantly improved electrochemical energy storage performance.